Heritage Stone 5. Silicified Granites (Bleeding Stone and Ochre Granite) as Global Heritage Stone Resources from Ávila, Central Spain - García-Talegón, Jacinta; Iñigo, Adolfo; Vicente-Tavera, Santiago; Molina-Ballesteros, Eloy (Geoscience Canada, 2016)
Silicified granites were used to build the Romanesque monuments in the city of Ávila, Spain. The building stones comprise two types of granite based on their technical properties and colour: Bleeding Stone (Piedra Sangrante) and Ochre Granite (Caleño). They were used as a facing stone in the city´s Romanesque monuments of the 12th century (e.g. the cathedral and church of San Pedro), and the famous city walls that constitute the best example of military Romanesque Spanish architecture. During the Gothic and Renaissance periods of the 13th and 15th centuries, silicified granites were used mainly to build ribbed vaults, the voissoirs of the arches, and elements of the windows in the monuments of Ávila. Silicified granites are found in the intermediate and upper part of a complex palaeoweathering zone or mantle developed on the Iberian Hercynian Basement which underlies much of the western Iberian Peninsula. The silicification occurred during tropical conditions in the Mesozoic. The weathered mantle was truncated by Alpine tectonic movements during the Tertiary, and its remnants were unconformably overlain by more recent sediments in the western and southern part of the Duero Basin and along the northern edge of the Amblés Valley graben. The historical, and now protected, quarry is located in a village called La Colilla, about 5 km from the city of Ávila. Currently, this stone is exploited only for restoration work performed in the city, for example the Walls of Ávila, and the church of San Pedro. The resource is limited and being depleted, so the stone will be scarce in the near future. Consequently, these silicified granites should be recognized as a Global Heritage Stone Resource. The specific technical properties of these stones and their historic use, decay patterns, durability, and suitability for conservation treatments combine to support its designation as a Global Heritage Stone Resource.